Job Design and Work Effectiveness : Determinants of Employee Performance - Tania Clarisa Karmelia; Iful Novianto; Ardiansyah Hendra Lukmana (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
The purpose of this study was to analyze the simultaneous effect of Job Design and Work Effectiveness on Employee Performance in Medical Record Staff at Bhakti Dharma Husada Hospital, Surabaya. This research approach uses a quantitative approach. The collection of research data was carried out using a questionnaire instrument. The formula used in this normality test is the Kolmogorov-Smirnov formula. The results of the Simultaneous Test (F Test) that have been carried out can be seen that simultaneously it has a positive and significant effect. Based on the data obtained and the results of statistical data tests that have been carried out, it can be concluded: Job Design and work effectiveness simultaneously have a significant effect on employee performance at Bhakti Dharma Husada Hospital.